2022
DOI: 10.3389/fpls.2022.920881
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-adapted heterologous symbiont Salinispora arenicola promotes growth and alleviates salt stress in tomato crop plants

Abstract: To ensure food security given the current scenario of climate change and the accompanying ecological repercussions, it is essential to search for new technologies and tools for agricultural production. Microorganism-based biostimulants are recognized as sustainable alternatives to traditional agrochemicals to enhance and protect agricultural production. Marine actinobacteria are a well-known source of novel compounds for biotechnological uses. In addition, former studies have suggested that coral symbiont acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The macronutrient (N, P, K, S, Mg, Ca, and Na) and micronutrient (Zn, Fe, Mn, and Cu) content were determined by the same method described in Section 3.1 . In addition, to corroborate that the salt contained in the algae powder did not affect the plants growth, the SlHB7 gene expression related to the response to salinity stress in tomato was performed according to the procedure described by Becerril–Espinosa et al [ 92 ].…”
Section: Methodsmentioning
confidence: 99%
“…The macronutrient (N, P, K, S, Mg, Ca, and Na) and micronutrient (Zn, Fe, Mn, and Cu) content were determined by the same method described in Section 3.1 . In addition, to corroborate that the salt contained in the algae powder did not affect the plants growth, the SlHB7 gene expression related to the response to salinity stress in tomato was performed according to the procedure described by Becerril–Espinosa et al [ 92 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, after learning that actinobacteria share a niche with a photosynthetic coral symbiont [4], we evaluated whether applying Salinispora arenicola, a symbiotic actinobacterium present in corals, would benefit the growth of terrestrial plants. We found that S. arenicola promoted the growth of tomato and wild tobacco plants while protecting them from salinity stress, highlighting its biotechnological potential for agricultural production [18,19]. In addition, the ability of actinobacteria to produce antibiotics is well known, with these organisms currently producing 45% of commercial antibiotics [20].…”
Section: Introductionmentioning
confidence: 92%
“…Coral samples of healthy adult colonies of Porites lobata (PL), Porites panamensis (PP), and Pavona gigantea (PG) were collected from several tropical coral ecosystems in the central Mexican Pacific (19 C and transported to the laboratory. Once in the laboratory, the seawater and mucus secretions on the surface of the coral samples were removed.…”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation